Dislocations in nanostructured two‐phase Fe30Ni20Mn20Al30. Issue 3 (19th January 2013) - Wu, X.; Baker, I.
ABSTRACT In a previous study, the dislocations in Fe30Ni20Mn25Al25 (at. %), which consist of 50 nm wide alternating b.c.c. and B2 phases, were shown to have a/2<111> Burgers vectors after room temperature deformation. The dislocations were found to glide in pairs on both 110 and 112 slip planes and were relatively widely separated in the b.c.c. phase, where the dislocations were uncoupled, and closely spaced in the B2 phase, where the dislocations were connected by an anti‐phase boundary. In this article, we analyze the dislocations in the two ∼5 nm‐wide B2 phases in a related two‐phase alloy Fe30Ni20Mn20Al30, with compositions Fe‐23Ni‐21Mn‐24Al and Fe‐39Ni‐12Mn‐34Al, compressed to ∼3% strain at a strain rate 5 × 10−4 s−1 at 873 K (the lowest temperature at which substantial plastic flow was observed). It is shown that slip occursby the glide of a<100> dislocations. A review of the literature suggests that the differences in the observed slip vector between these B2 phases could be due to the differences in composition, differences in deformation temperature, or possibly both. Microsc. Res. Tech. 76:263–267, 2013. © 2013 Wiley Periodicals, Inc.